Neuroimaging: biochemical principles and its application in the cerebrovascular ischemic disease. - Zenaida Milagros Hernández Díaz; Adnolys Reyes-Berazaín; Miguel Ángel Buergo -Zuaznabar; Marianela Arteche-Prior (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
The knowledge of neurobiochemical principles has allowed understanding the ischemic cascade that takes place after the decrease of cerebral blood flow and the findings that are visualized in neuroimaging studies in cerebrovascular ischemic disease. The need for early diagnosis of acute events to reestablish the cerebral blood flow to reduce neurological sequels, has led to the development of advanced imaging techniques, which allows following the histochemical and morphological changes that take place within the brain in vivo, in a non-invasive way, as well as its development, extent of the cerebral damage and damaged cerebral structures. The present bibliographic review has the objective of supporting the importance of neuroimaging studies in the diagnosis of acute cerebral ischemia.